Reducing Mortality and Morbidity in Morbidly Adherent Placenta - Rehana Taskeen, Durri Shahwar, Iram Rafique, Sabeeha Khan, Humaira Bashir, Rubina Baber, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The goal of this study is to explore methods for minimizing mortality and morbidity in the context of a morbidly adherent placenta. Study Design: A descriptive observational case series. Place and Duration: This is two-year study was held in the Obstetrics and Gynecology department of Khyber Teaching Hospital Peshawar from January 2018 to January 2020. Methods: There are 36 females included in this study who have morbidly adherent placenta. The surgical procedure, antenatal diagnosis, quantity of blood loss, organ damage, blood transfusion, hospitalization, ICU and postnatal problems are all evaluated in these patients. SPSS version 21 was used to analyze and evaluate the data. Results: Ultrasound and colour Doppler were used to diagnose 30 patients antenatally. Six of them were revealed during surgery, nine of them had a severe hemorrhage, and five to ten units of blood were transfused. Three of the undiagnosed patients suffered a bladder injury, ten were admitted to the hospital, and two required ventilator support. In 26 patients, hysterectomy was performed, while four patients had conservative surgery. There were no cases of maternal or newborn death. Conclusion: Mortality and Morbidity may be reduced by increasing the index of suspicion, performing prenatal diagnostics, anticipating large volume blood transfusions, and performing planned hysterectomy with a fundal classical incision without disturbing the placenta. It is important to be aware of the possibility of a morbidly adherent placenta, just as it is important to be aware of other obstetric crises.